A case of cerebral sinus venous thrombosis resulting in mortality in pregnant woman: late diagnosis (Indian Journal of Case Reports, 2019)
Cerebral venous sinus thrombosis (CVST) is a rare condition. The most frequent symptoms and signs are headache, focal seizures with or without secondary generalization, unilateral or bilateral paresis and papilledema. We report a case of CVST in a 30-yearold female that presented with headache, diminution of vision, swelling and pain in both eyes and bilateral restricted extraocular movements. She expired after 3 days of treatment as she was diagnosed late. Due to its diverse and varied clinical presentation, CVST should be considered as differential in almost any brain syndrome.